Metastasis-associated protein 1: a druggable target in cancer treatment - Madhusudana Pulaganti; Kireeti Anthati Soma; Rekha Mandla; Bhavana Cherukuthota; Haseena Dudekula (Korean Journal of Clinical Oncology)
Cancer treatment has undergone significant transformation with the emergence of molecularly targeted drugs, aiming to exploit specific vulnerabilities within cancer cells while sparing normal tissues. One critical aspect of this approach is the identification of druggable targets, proteins or pathways that can be modulated by pharmacological agents to inhibit tumor growth or metastasis. The metastasis-associated protein 1 (MTA1) has emerged as a promising druggable target due to its multifaceted roles in cancer progression, including regulation of gene expression, chromatin remodeling, and promotion of epithelial-mesenchymal transition. This abstract provides an overview of the current landscape of MTA1 as a druggable target in cancer therapy, highlighting its diverse functions across different malignancies and its potential as a predictive biomarker for therapeutic response. Finally, it explores future directions and novel strategies for exploiting MTA1 inhibition in precision oncology. Overall, understanding the druggable potential of MTA1 offers new avenues for the development of innovative cancer treatments with improved efficacy and reduced toxicity, ultimately leading to better clinical outcomes for cancer patients.